Initial public offering lockup expirations and insider selling. - Peh, Hwee Hwee. (2008)
We examine the microstructure effects of U.S. initial public offering (IPO) lockup expirations in the period of 1998-200 1 for a sample of technology firms. Most IPOs feature lockup agreements, which bar insiders from selling their share holdings for a period, typically 180 days.